2018
DOI: 10.1002/app.46877
|View full text |Cite
|
Sign up to set email alerts
|

Crystallinity and morphology of barium titanate filled poly(vinylidene fluoride) nanocomposites

Abstract: In this study, crystallization behavior and micromorphology of barium titanate (BaTiO3, or BT) filled poly(vinylidene fluoride) (PVDF) nanocomposites were investigated based on Fourier‐transform infrared spectroscopy (FTIR), polarized optical microscopy (POM), differential scanning calorimetry (DSC), and X‐ray diffractometry (XRD). BT/PVDF nanocomposite films with different concentrations of BT nanoparticles were prepared by solution casting method. The results revealed that the electrical conductivity and See… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…PerkinElmer (Waltham, MA, USA) Fourier transform infrared spectroscopy (FTIR) was used to determine the chemical structure and crystallinity of the printed films. A PerkinElmer DSC 8500 (Waltham, MA, USA) with an autosampler was used to investigate thermal behavior and the degree of crystallinity of the nanocomposite, according to the equation below: where x c is the degree of crystallinity, x is the mass fraction of PVDF in the nanocomposite, Δ H m is the melting enthalpy, and Δ H %100 is the melting enthalpy of a pure crystalline polymer, which is 104.6 J g −1 for PVDF [ 21 ]. Both heating and cooling measurements were carried out in the temperature range of 20–250 °C with a rate of 10 K min −1 .…”
Section: Methodsmentioning
confidence: 99%
“…PerkinElmer (Waltham, MA, USA) Fourier transform infrared spectroscopy (FTIR) was used to determine the chemical structure and crystallinity of the printed films. A PerkinElmer DSC 8500 (Waltham, MA, USA) with an autosampler was used to investigate thermal behavior and the degree of crystallinity of the nanocomposite, according to the equation below: where x c is the degree of crystallinity, x is the mass fraction of PVDF in the nanocomposite, Δ H m is the melting enthalpy, and Δ H %100 is the melting enthalpy of a pure crystalline polymer, which is 104.6 J g −1 for PVDF [ 21 ]. Both heating and cooling measurements were carried out in the temperature range of 20–250 °C with a rate of 10 K min −1 .…”
Section: Methodsmentioning
confidence: 99%
“…[8] In fact, antiparallel arrangement of dipoles in the α from makes it nonpolar and inactive in terms of piezoelectric activity while arrangement of highly electronegative fluorine atoms in one side of the polymer backbone in the β phase results in largest momentary polarization per unit cell (approximately 8 × 10 −30 C m −2 ) and the highest piezoelectric coefficient (|d 33 | = 34 pC N −1 ). [4,9] Therefore, α phase suppression and β phase enhancement is of great importance for broadening practical applications of PVDF. [9][10][11][12][13][14] In this regard, several studies tried to induce and enhance β phase content by uniaxial or biaxial stretching at high cooling rates, applying extremely high electric fields to the crystalline α phase and film-casting via polar solvents.…”
Section: Introductionmentioning
confidence: 99%
“…[4,9] Therefore, α phase suppression and β phase enhancement is of great importance for broadening practical applications of PVDF. [9][10][11][12][13][14] In this regard, several studies tried to induce and enhance β phase content by uniaxial or biaxial stretching at high cooling rates, applying extremely high electric fields to the crystalline α phase and film-casting via polar solvents. In addition, incorporating functional nanofillers such as barium titanate, [15] barium strontium titanate (BaSrTiO 3 ), lead zirconate titanate (PbZrTiO 3 ), [16] carbon nanotube, [17] nanoclay, [18] graphene oxide (GO), ferrites, [19] titania (TiO 2 ), and bismuth vanadate (BiVO4 4 ) into the PVDF matrix is an efficient and cost-effective approach to induce β polymorph.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Incorporating various ceramic 8 or conductive 9,10 nanofillers have been extensively studied in the literature in order to improve the relative amount of β phase. Barium titanate (BT) ceramic nanofillers with high dielectric constant improve the dielectric properties of the polymeric matrix [11][12][13][14][15] ; however, it is shown that by refining nanofiller size to nanometer scale, its dielectric permittivity drops down due to transition from tetragonal to cubic structure, 16 thus, higher amounts of BT is required to achieve the desirable improvement which negatively affects the dispersion quality, flexibility and mechanical performance of the composite. 9,11 On the other hand, the dielectric constant of the nanocomposite enhances markedly near the percolation threshold of conductive nanofillers such as carbon nanotubes (CNT), while yet, the increased electrical conductivity reduces the dielectric strength of the system markedly.…”
mentioning
confidence: 99%